The three versions of the ultimatum game an example from the history of creation of the Kingdom of Serbs, Croats and Slovenes 1914-1918 - Pavlović, Dušan, politolog; Đurašković, Stevo (2021)
We examine the 1914-1918 creation of the Kingdom of Serbs, Croats and Slovenes as a form of the ultimatum game.  The negotiations among the Serbian Cabinet and the yugoslav Committee representatives of the Habsburg Souths Slavs from 1914-1918 exemplify three versions of this game.  The first version is a typical (rational choice) type of the ultimatum game in which the  receiver is satisfied with any offer by the Proposer.  The second version is an instance of behavioral game theory.  When the Proposer gives an unfair offer, it provokes an emotional reaction in the  receiver who will reject it at the cost of harming themselves.  We observe this behavior in the emotional behavior of  frano Supilo, a Croat and one of the leaders of the  yugoslav Committee.  The third version of the behavioral ultimatum game  can  be  observed  in  the  behavior  of  Serbian  Prime  minister  nikola  Pašić  who opposed any concessions to the  yugoslav Committee, thus giving an ultimatum to the Croat side to accept the Serbian offer or remain with nothing, which was harmful to the Serbian side, too.  This example is important because it produces two conclusions.  first, historical games are often a mixture of several versions. Second, Proposers, too, can have an emotional reaction and  give an offer that can hurt themselves. This aspect  of the ultimatum  game is less  mentioned because it is  difficult to simulate in experiments.
U članku se analizira stvaranje Kraljevine Srba, Hrvata i Slovenaca 19141918  kao oblik  igre  ultimatuma.  rad  pokazuje  kako se  pregovori  između  Vlade Kraljevine Srbije i Jugoslavenskog odbora oko stvaranja zajedničke južnoslavenske države odvijaju putem triju verzija igre ultimatuma. Prva verzija je standardni model racionalnog izbora, gdje  Primatelj prihvaća svaku  ponudu  koju nudi  Ponuditelj. Druga verzija je primjer bihevioralne igre ultimatuma, gdje nekorektna ponuda Ponuditelja izaziva odbijanje od strane Primatelja pod cijenu štete koju trpi Primatelj. Članak pokazuje tu vrstu ponašanja na primjeru djelovanja  frane Supila, jednoga od vođa Jugoslavenskog odbora.  Treća verzija je primjer bihevioralne igre ultimatuma gdje ponuditelj inzistira na ponudi koje može ići na njegovu štetu.  ona se može uočiti u ponašanju srbijanskog premijera  nikole Pašića koji se usprotivio bilo kakvim ustupcima Jugoslavenskom odboru, dajući tako ultimatum hrvatskoj strani da prihvati srpsku ponudu ili ostane bez ičega, što bi bilo štetno i za srpsku stranu. ovaj primjer je važan jer upućuje na dva zaključka. Prvo, povijesne igre često su mješavina nekoliko verzija. Drugo, Ponuditelj također može imati emocionalnu reakciju i dati ponudu kojom može našteti sebi.  ovaj se aspekt igre ultimatuma manje spominje jer ga je teško simulirati u eksperimentima.
Bibliografske bilješke uz tekst ; bibliografija: str. 365-368.
Summary ; Sažetak.
Keywords: Prvi svjetski rat -- Pregovori; Jugoslavenski odbor; Kraljevina Srba, Hrvata i Slovenaca